A Factor That Can be Used to Regulate an In Vitro Primary Immune Response - Watson, James (1972)
A factor has been isolated that supports the stimulation of an immune response against heterologous erythrocyte antigens in mouse spleen cells cultured in a medium that contains deficient serum. The factor is secreted by certain spleen cells that are obtained in permanent culture after leukemia virus infection. The factor permits antigen-sensitive cells derived from bone marrow to mature to antibody-forming cells. This factor can be used in controlling the initiation of a primary immune response in vitro.